Chemical characterization and antimicrobial activities of Citrus aurantifolia peel oils and Ocimum sanctum ethanolic extract - Pintana Duangsombat; Neti Waranuch; Tasana Pitaksuteepong (PLoS ONE, 2025)
Oral diseases affect more than 3.5 billion people globally, representing a major public health burden, particularly in low- and middle-income countries where access to dental care is often limited. Furthermore, the use of conventional antimicrobial agent may cause side effect. This underscores the need for affordable, plant-based alternatives to conventional antimicrobials. This study investigated the chemical compositions and antimicrobial activities of Citrus aurantifolia peel oils from Thailand (Lime TH) and South Africa (Lime SF), along with an ethanolic extract of Ocimum sanctum L. (OSE), against five oral pathogens: Lactobacillus acidophilus, Streptococcus mutans, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Candida albicans. Chemical constituents were analyzed using gas chromatography-mass spectrometry (GC-MS) for the peel oils and high-performance liquid chromatography (HPLC) for the extract. GC-MS identified D-limonene as the major constituent in both Lime TH (49.11 ± 0.76% w/w) and Lime SF (42.32 ± 0.60% w/w), while HPLC confirmed the presence of ursolic acid in OSE (2.67 ± 0.07% w/w). Antimicrobial activity was evaluated by broth microdilution to determine minimum inhibitory concentrations (MIC), minimum bactericidal/fungicidal concentrations (MBC/MFC), and time-kill kinetics. Lime TH exhibited the strongest activity (MIC and MBC/MFC values between 0.20 and 25.0 mg/mL), followed by Lime SF (0.39–50.0 mg/mL). OSE inhibited four bacterial strains (excluding C. albicans) with MIC and MBC values ranging from 0.05 to 100 mg/mL. These findings highlight the potential of C. aurantifolia peel oils and O. sanctum extract as natural antimicrobial agents for incorporation into oral care products.